The effects of syllable boundary and context on word recognition in Korean continuous speech. (1st January 2014) - Kang, Jinwon; Nam, Kichun
We examined resyllabification cost in spoken word recognition in Korean and found an interaction between syllable boundary and context at the lexical level. Experiment 1 compared a misalignment condition and an alignment condition. The misalignment condition involves the word-final consonant merging with the onset of the next syllable. The alignment condition involves word-vowel match with syllable boundary. Experiment 1, in the word spotting task, showed faster and more accurate word recognition in the alignment than in the misalignment condition. Experiment 2 was conducted to investigate the effects of the syllable boundary as well as context on word recognition. Four types of target stimuli were created: target related-aligned, target related-misaligned, target neutral-aligned, and target neutral-misaligned. Experiment 2, auditory lexical decision task, showed an interaction between syllable boundary and context variables. Thus, we confirmed the syllable's role as a segmentation unit. Furthermore, the context and the syllable boundary significantly affected word recognition at the lexical level together.